(Bio)degradable polymeric materials for a sustainable future – part 1. Organic recycling of PLA/PBAT blends in the form of prototype packages with long shelf-life. (July 2018) - Musioł, Marta; Sikorska, Wanda; Janeczek, Henryk; Wałach, Wojciech; Hercog, Anna; Johnston, Brian; Rydz, Joanna
Highlights: Degradation behavior of packaging with commercial additives has been investigated. The talc greatly influences on the packaging water absorption and degradation profile. Talc may cause differences in water absorption depending on environment humidity. The influence of samples' shape on the degradation profile has been confirmed. The shelf life of the product can be adjusted by quantity of the commercial additive. Abstract: Prediction studies of advanced (bio)degradable polymeric materials are crucial when their potential applications as compostable products with long shelf-life is considered for today's market. The aim of this study was to determine the effect of the polylactide (PLA) content in the blends of PLA and poly(butylene adipate- co -terephthalate) (PBAT); specifically how the material's thickness corresponded to changes that occurred in products during the degradation process. Additionally, the influence of talc on the degradation profile of all samples in all environments was investigated. It was found that, differences in the degradation rate of materials tested with a similar content of the PLA component could be caused by differences in their thickness, the presence of commercial additives used during processing or a combination of both. The obtained results indicated that the presence of talc may interfere with materials behavior towards water and consequently alter their degradation profile.